Treatment of polycythaemia vera by radiophosphorus or busulphan: a randomized trial. "Leukemia and Hematosarcoma" Cooperative Group, European Organization for Research on Treatment of Cancer (E.O.R.T.C.). (Nature Publishing Group, 1981)
Between 1967 and 1978 a Phase III cooperative study was performed in polycythaemia vera (PCV) patients who had not been treated previously with any specific therapy other than phlebotomy. 293 patients were included and allocated at random for either radiophosphorus therapy (146) or busulphan treatment (147). Additional phlebotomies were indicated in both groups, to keep the haematocrit at 42-47%. 285 patients were evaluable after the study was completed, of whom 50% have an 8-year follow-up. Both groups were comparable with respect to age, clinical symptoms and haematological parameters immediately before randomization. The duration of the first remission and the overall survival were significantly better in the busulphan group. This difference remains significant after correction for differences between the two groups with respect to sex-ratio and phlebotomy before and the start of therapy. Busulphan induced a longer first remission (P less than 0.001) and a longer overall survival (P less than 0.02).